A new strategy to fight antimicrobial resistance: the revival of old antibiotics - Cassir, Nadim; Rolain, Jean-Marc; Brouqui, Philippe (Frontiers in Microbiology, 2014)
The increasing prevalence of hospital- and community-acquired infections caused by multidrug-resistant bacterial pathogens is limiting the options for effective antibiotic therapy. Moreover, this alarming spread of antimicrobial resistance has not been paralleled by the development of novel antimicrobials. Resistance to the scarce new antibiotics is also emerging. In this context, the rational use of older antibiotics could represent an alternative for the treatment of multidrug-resistant bacterial pathogens. This strategy would help to optimize the armamentarium of antibiotics so as to preserve the effectiveness of new antibiotics and avoid the prescription of drugs known to favor the spread of resistance (i.e., quinolones). Furthermore, from a global economic perspective, this strategy could be useful in public health, given that several of these cheapest “forgotten” antibiotics are not available in many countries. We will review here the successful treatment of multidrug-resistant bacterial infections with old antibiotics and discuss their place in current practice.